Innovative methodological strategies for Reading comprehension - Guerrero Guerrero, Héctor Ulpiano; Salvador Saráuz, Patricia Lorena (SATHIRI, 2022)
One of the most obvious difficulties in educational spaces is reading comprehension and the methodological strategies involved in the process since they directly affect the academic performance of students leaving them devoid of one of the social activities that keep the human being immersed in the culture, society, and environment in which he develops and lives. This research, defined from a qualitative approach, aims to investigate in scientific documents how they deploy innovative methodological strategies to improve the skills of reading comprehension in students. The study was carried out from the search for documentary bibliographic information through a qualitative analysis of the information; for this, the most relevant articles related to the topic of study in the last 5 years were selected, found in search engines such as Publish or Perish 7 and Google Scholar, as well as in repositories and scientific databases such as Redalyc, Scielo, Scopus and Dialnet. The review of the data showed that active strategies, the use of multimedia material, and the new limits of education are part of the innovative methodological strategies in which unidirectional classical education becomes obsolete before the proposal of education is understood as an act of social participation. In addition, it was identified that educational interaction is defined from the participation and collaboration of all, to build autonomous and free learners in the processes of knowledge generation. It proposes the redefinition of the idea of education based on the use of innovative methodological strategies that have transcended the traditional limits of education. Activities, roles, evaluation, interaction are some of the factors recognized as positive results in terms of improving reading comprehension in students. These innovative strategies, applied at various levels of training, agree that everything must opt for participatory, collaborative spaces that promote taking the school to other spaces in which knowledge is applied. The purpose of the text is proposed as the beginning of a fundamental discussion on the transformation of the educational structure.
Keywords: autonomy; understanding; strategies; excellence; methodologies